1984
DOI: 10.1002/ijc.2910330114
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoreticular cells isolated by centrifugal elutriation from a mammary adenocaricinoma. i. characterization of an in situ lymphocyte suppressor population by surface markers and functional reactivity

Abstract: The procedure of centrifugal elutriation was evaluated as a means of purifying large numbers of in situ lymphocytes from enzymatically disaggregated mouse mammary tumors. The eluate obtained at a flow rate of 3.0 ml/min was optimal for high levels of lymphocyte recovery with low levels of contaminating tumor cells, polymorphonuclear leukocytes, and macrophages. The majority of the tumor infiltrating lymphocytes (90%) expressed the Thy 1.2 antigen, while less than 5% possessed surface immunoglobulin. Further an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Our data agree with the reported phenotypic profile of infiltrates from human breast cancer, namely, a predominance of OKT8-positive lymphocytes and decrease in OKT4-positive lymphocytes, relative to peripheral lymphoid organs [26,30]. Phenotypic studies of TILs from other rodent tumors have generally been performed on long-term passaged tumors [2,10,16]. Lala and McKenzie [10] reported that lyt-2-positive cells were greatly increased in T1L relative to peripheral lymphoid organs in mice bearing MPC-11 plasmacytoma and WEHI-164 fibrosarcoma lines.…”
Section: Discussionsupporting
confidence: 93%
“…Our data agree with the reported phenotypic profile of infiltrates from human breast cancer, namely, a predominance of OKT8-positive lymphocytes and decrease in OKT4-positive lymphocytes, relative to peripheral lymphoid organs [26,30]. Phenotypic studies of TILs from other rodent tumors have generally been performed on long-term passaged tumors [2,10,16]. Lala and McKenzie [10] reported that lyt-2-positive cells were greatly increased in T1L relative to peripheral lymphoid organs in mice bearing MPC-11 plasmacytoma and WEHI-164 fibrosarcoma lines.…”
Section: Discussionsupporting
confidence: 93%
“…The up-regulated expression of MMP-9 is found not only in splenic T cells but, more importantly, in the T cells infiltrating the tumor microenvironment, and this increased expression correlates with tumor growth. Our previous studies (58) and those of many other investigators (19,59) have shown the infiltration of the tumor microenvironment by lymphocytes through a process involving adhesion molecules (60). The presence of MMP-9 in tumor bearers' lymphocytes may also play a role, because this metalloproteinase has the potential to degrade matrix protein and to promote leukocyte traffic.…”
Section: Discussionmentioning
confidence: 84%
“…is, however, still unclear (Miescher et al, 1986). For example, CD8+ (Lyt 2 + ) T effector cells can be found at tumor sites (Vollmer et al, 1986;Whiteside et al, 1986~;Buessow et a[., 1984b), but are often functionally inactive when isolated and tested in vitro.…”
Section: Discussionmentioning
confidence: 99%